2020
DOI: 10.1093/mnras/staa3073
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a new ultraluminous X-ray source in NGC 1316

Abstract: In this study, we report identification of a new ultraluminous X-ray source (ULX) named as X-7 in NGC 1316, with an unabsorbed luminosity of 2.1× 1039 erg s−1 using the two recent Chandra archival observations. The X-7 was detected in the Chandra 2001 observation and was included in the source list of the NGC 1316 as CXOUJ032240.8-371224 with a luminosity of 5.7× 1038 erg s−1. Present luminosity implies a luminosity increase of a factor of ∼ 4. The best fit spectral model parameters indicate that X-7 has a rel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…X-ray coordinates of the three ULXs and lower X-ray luminosity sources coincident with candidate globular clusters. These sources have been identified in Kim & Fabbiano (2003), Swartz et al (2004), andAllak et al (2020). Sources marked with 𝑜 were identified by Goudfrooij et al (2001b), sources with † were identified by Jordán et al (2016) tbabs*(diskbb+pegpwrlw) to the deep spectra, however, only GCULX2 could be fit by the two component model.…”
Section: X-ray Analysismentioning
confidence: 98%
See 1 more Smart Citation
“…X-ray coordinates of the three ULXs and lower X-ray luminosity sources coincident with candidate globular clusters. These sources have been identified in Kim & Fabbiano (2003), Swartz et al (2004), andAllak et al (2020). Sources marked with 𝑜 were identified by Goudfrooij et al (2001b), sources with † were identified by Jordán et al (2016) tbabs*(diskbb+pegpwrlw) to the deep spectra, however, only GCULX2 could be fit by the two component model.…”
Section: X-ray Analysismentioning
confidence: 98%
“…Two ULX sources, GCULX1 and GCULX2, match to globular cluster candidates in the Jordán et al (2016) survey. GCULX3's optical counterpart, identified in Allak et al (2020), also had characteristics typical of extragalactic globular clusters. We use DAOPHOT (Stetson 1987) to perform photometry on all three sources, as well as other known GCs in the field, using images that corresponds to the 𝑔, 𝑧 bands, and found that GCULX3's colour and magnitude are typical for a globular cluster.…”
Section: Hst Analysis and Globular Cluster Counterpart Identificationmentioning
confidence: 99%
“…We used HST archival data (see Table 3 for details) to investigate the optical properties of ULX-4. For a relative astrometry between Chandra (ObsID 13816) and HST (ObsID J97C51R4Q) images, we followed a similar method that we used in our previous works (Allak et al 2020;Ozdogan Ela et al 2021). The tool in 7 and wavedetect tool in were used for source detection in HST and Chandra images, respectively.…”
Section: Astrometrymentioning
confidence: 99%
“…This is likely to increase the discovery of new transit sources as well (e.g. Middleton et al 2012;Barnard et al 2013;Hu et al 2018;van Haaften et al 2019;Allak et al 2020;Walton et al 2021). PULXs are observed sources in this class with their high flux variability reaching up to factors of 50 in flux variation.…”
mentioning
confidence: 99%
See 1 more Smart Citation